Boundary concepts for interdisciplinary analysis of irrigation water management in South Asia - Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2010)
This paper reviews the boundary concepts that have emerged in interdisciplinary irrigation studies in South Asia, particularly India. The focus is concepts that capture the hybridity of irrigation systems as complex systems, and cross the boundaries of the natural and social sciences. Concepts capturing the materialisation of rights, design-management relations and the social construction of technology, the notions of landesque capital and (the valuation of) ecosystem goods and services, and finally the broader issues of space-time relations and a cultural politics of water, are explored. The paper takes the analysis forward by suggesting starting points for more comprehensive interdisciplinary social theory on irrigation. On the side of formal theory a focus on a combination the emerging concept of hydrosocial cycle with structure-agency theorisation as morphogenesis is proposed; on the side of substantive theory three avenues for investigation of the materiality of the social process of irrigation are proposed in the commodity form, a materialist institutionalism and the embodiment of agency. The paper concludes by listing five further research activities.
Keywords: 330; interdisciplinarity; India; irrigation; boundary concepts; technology; landscapes